Impact of Nasal Anatomical Variation Subtype on Surgical Outcomes for Rhinogenic Contact Point Headache - Salvatore Lavalle; Annalisa Pace; Giuseppe Magliulo; Mario Lentini; Jerome Rene Lechien; Christian Calvo-Henriquez; Federica Maria Parisi; Giannicola Iannella; Antonino Maniaci; Daniela Messineo (Diagnostics, 2025)
Background/Objectives: Rhinogenic contact point headache (RCPH) is a controversial secondary headache disorder involving mucosal contact points in the nasal sinuses. The efficacy of surgical versus medical management has been debated, with some studies showing excellent long-term outcomes but others citing placebo effects. This study aimed to clarify the correlation with nasal anatomical variation detected by CT and RCPH treatment outcomes. Methods: A prospective cohort study was conducted on 90 RCPH patients undergoing surgery or medical therapy. Patients were diagnosed using CT scans, endoscopy, and lidocaine testing. The surgery group had endoscopic procedures to remove contact points. The medical group received intranasal steroids. Outcomes were measured by visual analog scale (VAS) for pain and headache frequency. Predictors like age, gender, and nasal anatomical variations were analyzed. Results: The surgery group showed significant reductions in VAS scores (6.02 to 2.51, p < 0.001) and headache frequency (9.11 to 3.04, p < 0.001). The medical group did not improve significantly. All nasal subtypes improved with surgery but concha bullosa had worse VAS outcomes (4.0) than septal deviation (1.8, p < 0.001) or spur (1.73, p < 0.001). Multivariate analysis found nasal anomalies predicted postoperative VAS scores (p < 0.001) but not headache frequency (p = 0.255). Conclusions: Surgery demonstrated superiority over medications for RCPH. This study provides new evidence that preoperative CT scans should be considered a non-invasive gold standard for analyzing nasal subtypes as they significantly influence surgical success, with concha bullosa associated with worse pain relief. Larger studies should validate these findings to optimize RCPH management.